Получение углеродных нанотрубок из природного газа - Жерлицын А. Г. Алексей Григорьевич; Косицын В. С. Виктор Сергеевич; Кобец А. С. Анна Сергеевна; Постников П. С. Павел Сергеевич; Трусова М. Е. Марина Евгеньевна; Шиян В. П. Владимир Петрович (Физика. Математика, 2012)
Заглавие с титульного листа